Analisis Ratio Keuangan terhadap Perubahan Kinerja pada Perusahaan di Industri Food and Baverages yang Terdaftar pada BEJ - DIAN MERIEWATY; ASTUTI YULI SEIYANI (Fakultas Bisnis UKDW, 2005)
Financial statements users need financial informotion of companies to analyze their financial condition and performance. Finacial rotios are useful rneasares for explaning the future earning changes. The study focuses on the usefulness of ftnancial ratios in explaning future eamings.The objective of the study is to empirically examine whether financial statement based tinancial ratios hove ability for explaning future earnings. Data in this study were in food and beverages firms listed on the Jaknrta Stock Exchange. Regression analysis were used in testing the ability financial ratios for explaning changes. The multicollinearity test shows that there is no assosiation between independent variables, indicating multieollinearity is not a seriaus problem. The heteroscedasticity test shows that voriances of disturbances are constant for all observation in independentt variables. Therefore heteroscedasticity is not a problem. The empiricolly result showed that, financial ratios in/luences the futureearnings changes for earning after tax are total debt to total capital assets, total assets turnover, and return on investment. Among those sevent financial ratios that are significant influences the future earnings changes for operating prortt is current ratio.Keywords : Financial Ratios, Performance changes of firms, significantlyinfluence.